Efficiency of microorganisms (em) in the functional improvement of the digestive system of pigs in post-weaning phase - Cortés Machado, Luz; Gómez Torres, Fabián Alejandro (Spei Domus, 2011)
The porcine industry grows everyday worldwide, this leads every exploitation to seek the reduction of its production costs and the improvement of its production levels. With this in mind, the objective of this research project is to evaluate the efficiency of microorganisms (em) in the functional improvement of the digestive system of suckling pigs, with the evaluation of zootechnical parameters such as weight gain, consumption and conversion. This research project, entitled “The efficiency of microorganisms in the functional improvement of the digestive system of suckling pigs” was carried out in the Villa Porkinos pig farm in the La Puente township of the municipality of Lebrija, Santander, in 2010. We chose four lots of pigs in suckling phase to be fed em and 2 more lots as a control group. Zootechnical performance was evaluated on the fourth week. We observed that the control group had an average weight gain of 18.9 kilograms, whereas the treated group gained 18.3 kg on average. The control lots had an average conversion of 1.34 with an average daily food consumption of 567.5 g; treated lots had a conversion of 1.11 with an average daily consumption of 529.65 g. All this leads us to think that the inclusion of efficient microorganisms in the diet of suckling pigs is favorable to the increase of conversion indexes in these pigs, since the treated group had better consumption than the control group. Although weight gain was higher in the control group, their consumption was also higher thus lowering their conversion rate.